Identity Construction of Otaku and Weeaboo through Manga and Anime - Louis Adhitama (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Manga and Anime are known as the most famous Japanese works among their fans, otaku and weeaboo. Nowadays, it is easier to access manga and anime through the internet, and these works can influence otakus and weeaboos’ identity construction. This research is written to know the characteristics of otaku and weeaboo, the reasons why they identify themselves as otaku and weeaboo, and what method that otaku and weeaboo use to construct their virtual identity. This thesis uses a method of qualitative research and gathers all data by interviewing four informants with structured questions. Social identity by Henri Tajfel and identity theory in the virtual world by B. Coleman are used to connect the data from informants with the analysis. Through the theory application, there are some discoveries which relate to otaku and weeaboo. They have two main characteristics as information-fetishists and being obsessed with having merchandise which relate to manga and anime. Furthermore, the reasons otaku and weeaboo construct their virtual identity are improving themselves in the real world by exploring manga and anime characters and creating an ideal world in a virtual world for sharing the same obsession with each other. Moreover, otaku and weeaboo create avatars and memes as a way to show their constructed virtual identity and develop their talents. Keywords: manga and anime, identity construction, otaku and weeaboo, information-fetishist, virtual